(untitled) (Journal of Applied Oral Science, 2011)
OBJECTIVES: This study evaluated the effects of coronally positioned flap (CPF) on the subgingival biofilm composition. MATERIAL AND METHODS: Twenty-two subjects with gingival recessions were treated with CPF. Clinical parameters were assessed before and at 6 months after surgery. Subgingival biofilms were analyzed by checkerboard DNA-DNA hybridization technique for 40 bacterial species. RESULTS: Recession height, clinical attachment level and bleeding on probing improved significantly (p